High-flux composite membrane for high-efficiency separation of gas mixture as well as preparation method and application of high-flux composite membrane
By controlling the prepolymerization degree and initial molecular weight of the PDMS casting membrane liquid, ensuring its retention rate on the supporting ultrafiltration membrane, and combining atmospheric plasma treatment, the problems of low flux and poor selectivity of the composite membrane are solved, and efficient and economical gas mixture separation effect is achieved.
Patent Information
- Application Number
- CN202510183019.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-19
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-02-19
AI Technical Summary
The existing composite membranes have low flux and poor selectivity during the gas mixture separation process, and the preparation process is complex and costly.
By controlling the prepolymerization degree of PDMS casting membrane liquid and the initial PDMS molecular weight, it ensures that its retention rate on the ultrafiltration membrane of the support layer is greater than or equal to 90%, avoid pore seepage, and use atmospheric plasma to treat the modified PDMS surface to improve the wettability of the Pebax selection layer.
High throughput and high selectivity gas mixture separation is achieved, reducing material cost and preparation complexity, while expanding the processing area, suitable for industrial production.
Smart Images

Figure CN119793235A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the field of membrane separation technology, and more specifically, relates to a high-throughput composite membrane for efficient separation of gas mixtures, a preparation method thereof, and applications thereof. Background Art
[0002] With the development of economy and society, people's requirements for living environment and their own health are increasing day by day. Volatile organic compounds (VOCs) are an important atmospheric pollutant. Indiscriminate emission will have a negative impact on human health and environmental ecology. The tail gas in the polypropylene synthesis process contains 15-25% propylene and 75-85% nitrogen. Propylene is a VOCs with important recycling value, so the separation of propylene and nitrogen is of great significance for resource recovery and ecological environment protection. Carbon dioxide, as the most important greenhouse gas, mainly comes from the combustion of fossil fuels. The global warming potential of methane is 34 times that of carbon dioxide, and it is considered to be second only to carbon dioxide in global warming contribution. The main sources of methane emissions include fossil fuels and biogas in animal husbandry.
[0003] Membrane separation technology is expected to reduce separation energy consumption and operating costs due to its advantages such as no phase change in the separation process, small footprint, simple operation and maintenance. In practical applications, in order to improve the processing capacity, gas separation membranes are mostly composite membrane structures, which consist of three parts: a selective layer that provides separation selectivity, a high-permeability intermediate layer, and a porous support layer that provides mechanical strength. According to the series resistance model, a high-flux intermediate layer is the basis of a high-flux composite membrane. However, during the preparation of the intermediate layer, the low-concentration casting solution will inevitably penetrate into the pores of the porous support layer. The pore permeation phenomenon leads to an increase in the actual thickness of the intermediate layer and a decrease in flux. Although increasing the concentration of the casting solution can reduce the pore permeation to a certain extent, it will also increase the thickness of the PDMS layer and reduce the flux. Taking polydimethylsiloxane (PDMS), the most common intermediate layer material, as an example, in order to prevent pore permeation, the current strategy is to modify the end groups of PDMS to achieve rapid cross-linking of PDMS. However, this method will increase the material cost and complicate the preparation process. At the same time, the preparation of Pebax composite membranes only stays in small-area preparation, and there is a problem of difficulty in scale-up. The reason is that the hydrophilic Pebax is difficult to load evenly on the hydrophobic PDMS surface, and the currently used oxygen plasma hydrophilic treatment is limited by equipment and the treatment area, which restricts its large-scale production. Summary of the invention
[0004] In view of the defects of the prior art, the purpose of the present application is to provide a high-flux composite membrane for efficient separation of gas mixtures, its preparation method and application, aiming to solve the technical problems of low gas flux and / or poor selectivity when the composite membranes of the prior art are used for separation of gas mixtures.
[0005] To achieve the above objectives, in a first aspect, the present application provides a method for preparing a high-flux composite membrane for efficient separation of gas mixtures, comprising the following steps: (1) dissolving an initial hydroxyl-terminated polydimethylsiloxane (PDMS), a crosslinking agent, and a catalyst in a first solvent, mixing and stirring to allow the initial hydroxyl-terminated polydimethylsiloxane to undergo a prepolymerization reaction to obtain a PDMS casting solution; (2) using the porous ultrafiltration membrane as a suction filtration membrane of a dead-end filtration system, and testing the retention rate of the porous ultrafiltration membrane for the PDMS casting solution of step (1); (3) If the retention rate measured in step (2) is greater than or equal to 90%, proceed to step (4); otherwise, increase the degree of prepolymerization of the PDMS casting solution in step (1) or increase the molecular weight of the initial hydroxyl-terminated polydimethylsiloxane, so that the retention rate of the casting solution obtained after the prepolymerization reaction measured in step (2) is greater than or equal to 90%; (4) transferring the PDMS casting solution corresponding to the measured retention rate greater than or equal to 90% to the surface of the supporting layer ultrafiltration membrane, scraping and drying to remove excess first solvent, thereby obtaining a PDMS membrane; the supporting layer ultrafiltration membrane and the porous ultrafiltration membrane of step (2) are ultrafiltration membranes of the same model; (5) dissolving polyether block polyamide (Pebax) in a second solvent to obtain a Pebax casting solution; transferring the Pebax casting solution to the surface of the PDMS membrane, scraping and drying to remove excess second solvent, and preparing a Pebax selection layer on the surface of the PDMS membrane, thereby obtaining the high-throughput composite membrane.
[0006] Preferably, in step (2), the porous ultrafiltration membrane is used as the suction filtration membrane of the dead-end filtration system, and the retention rate is calculated by analyzing the PDMS concentrations in the initial PDMS casting solution and the PDMS casting solution on the permeate side before and after filtration of the dead-end filtration system using nuclear magnetic resonance hydrogen spectrum.
[0007] Preferably, the concentration of PDMS in the test solution is calculated by the area normalization method based on the characteristic hydrogen atom peak areas of PDMS in the test solution and the first solvent, wherein the test solution includes the initial PDMS casting solution and the PDMS casting solution on the osmotic side; the concentration calculation formula of PDMS in the test solution is as shown in formula (1):
[0008] Where: c i is the concentration of PDMS in the test solution, wt%; A i and A k Respectively represent the characteristic hydrogen atom peak areas of PDMS and the first solvent in the test solution; n i and n kRespectively represent the characteristic hydrogen atoms of PDMS and the first solvent in the test solution; m i and m k Respectively represent the relative molecular weights of PDMS and the first solvent in the test solution.
[0009] Preferably, step (3) increases the degree of prepolymerization of the PDMS casting solution in step (1) so that the retention rate of the casting solution obtained after the prepolymerization reaction measured in step (2) is greater than or equal to 90%, specifically: the degree of prepolymerization is increased by extending the time of the prepolymerization reaction in step (1) so that the retention rate of the casting solution is greater than or equal to 90%, or the molecular weight of the initial PDMS is increased so that the retention rate of the casting solution is greater than or equal to 90%. Preferably, after obtaining the PDMS membrane in step (4), the method further comprises the step of: using an atmospheric plasma cleaning machine to perform hydrophilic modification on the surface of the PDMS membrane to obtain a hydrophilically modified PDMS membrane.
[0010] According to another aspect of the present invention, a high-flux composite membrane prepared by the preparation method is provided.
[0011] According to another aspect of the present invention, there is provided a use of the high-flux composite membrane in separation of gas mixtures.
[0012] In general, the above technical solutions conceived by this application have the following beneficial effects compared with the prior art: (1) The present invention provides a method for preparing a high-throughput composite membrane for efficient separation of gas mixtures. By specifically controlling the prepolymerization degree of the PDMS casting solution or the molecular weight of the initial PDMS, the retention rate of the casting solution on the surface of the selected support layer ultrafiltration membrane is greater than or equal to 90%. The quantitative retention rate is cleverly used to reflect the porosity, thereby solving the porosity problem of PDMS in the support layer, and further preparing a high-throughput and high-selectivity Pebax composite membrane.
[0013] (2) The present invention provides a high-throughput composite membrane for efficient separation of gas mixtures, comprising a selective layer, an intermediate layer and a porous support layer arranged in sequence along the air inlet direction, wherein the porous support layer is a commercial ultrafiltration membrane; the intermediate layer is a polydimethylsiloxane film; the selective layer is a polyether block polyamide film; and the retention rate of the intermediate layer casting liquid in the support layer is controlled to be greater than or equal to 90%. The present invention experimentally found that when the retention rate of the PDMS casting liquid in the support layer in the composite membrane is controlled to be greater than or equal to 90%, the PDMS can be retained by the substrate as much as possible on the surface of the support layer, thereby avoiding the pore permeation phenomenon. In the preferred embodiment, atmospheric plasma treatment is simultaneously used to hydrophilically modify the PDMS surface, and hydrophilic groups such as hydroxyl groups are introduced on the surface to improve the affinity between the intermediate layer and the Pebax selective layer, so as to prepare a high-throughput Pebax composite membrane.
[0014] (3) The method of the present invention does not limit the initial PDMS molecular weight, nor does it limit the retention molecular weight of the porous support layer. It only needs to control the prepolymerization degree of PDMS in the casting solution and, with the help of the retention rate test formula proposed in the present invention, control the retention rate to be greater than or equal to 90% to prepare the composite membrane, thereby effectively avoiding the pore permeation phenomenon and improving the flux and selectivity of the mixed gas.
[0015] (4) The atmospheric plasma cleaning machine used in the method of the present invention can improve the wettability of the Pebax casting solution on the PDMS surface, thereby preparing an ultra-thin Pebax selective layer. At the same time, the method of the present invention also has a large treatment area (up to 1200 cm 2 ), has advantages such as good treatment effect and industrial scale-up, while the existing technology commonly uses oxygen plasma cleaning machines, which are complicated to operate and have a small treatment area due to equipment limitations.
[0016] (5) The selective layer material of the composite membrane prepared by the method of the present invention is Pebax, which has high selectivity and good plasticization resistance. In addition, since Pebax has good affinity with the modified intermediate layer, the thickness of the obtained selective layer is thinner and it also has the advantage of high gas flux. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 This is the result of H NMR spectrum test of the permeate side solution of PDMS with different molecular weights (15kDa-347kDa) intercepted by the PSF support layer (molecular weight cutoff: 63kDa) collected by dead-end filtration.
[0018] Figure 2 Figure 3 is the retention rate of PSF support layer (MWCO: 63 kDa and 20 kDa) for PDMS with different molecular weights (15 kDa-347 kDa) in dead-end filtration test.
[0019] Figure 3 This is a scanning electron microscope photograph of the cross-section of the intermediate layer material of the PDMS composite membrane prepared by PDMS with different molecular weights tested by the filtration method.
[0020] Figure 4 The carbon dioxide / nitrogen pure gas separation performance of the PDMS composite membranes prepared in Example 1 with different prepolymerization times.
[0021] Figure 5 The carbon dioxide / nitrogen pure gas separation performance of the PDMS composite membrane prepared in Example 1 at different prepolymerization times of 0 and 30 minutes.
[0022] Figure 6 1 is a scanning electron microscope photograph of the surface and cross section of the PDMS composite membrane with a prepolymerization time of 30 min in Example 1.
[0023] Figure 7 This is the change in the retention rate of PDMS by the PSF support layer before and after 30 minutes of prepolymerization.
[0024] Figure 8 is the change of carbon dioxide flux and water contact angle after atmospheric plasma treatment on PDMS surface.
[0025] Fig. 9 is a scanning electron microscope photo, where Fig. 9 Content (a) is a scanning electron microscope photo of the surface of the PSF ultrafiltration membrane in Example 1. Fig. 9 Content (b) and content (c) are scanning electron microscope photographs of the surface and cross section of the Pebax composite film obtained in Example 1, respectively.
[0026] Fig.10 The pure gas flux of the Pebax composite membrane prepared in Example 1 to different gases.
[0027] Fig.11 The changes in gas flux and propylene / nitrogen selectivity of the Pebax composite membrane prepared in Example 1 were tested for 80 hours of mixed gas.
[0028] Fig.12 The separation performance of the Pebax composite membrane prepared in Example 1 for a mixed gas of carbon dioxide / methane. DETAILED DESCRIPTION
[0029] In order to make the purpose, technical solution and advantages of the present application more clearly understood, the present application is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.
[0030] The embodiments of the present invention are implemented on the premise of the technical solution of the present invention, and detailed implementation methods and processes are given, but the protection scope of the present invention is not limited to the following embodiments. The process parameters of the following embodiments that do not specify specific conditions are usually based on conventional conditions.
[0031] The endpoints and any values of the ranges disclosed in the present invention are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in the present invention.
[0032] The present invention provides a method for preparing a high-throughput composite membrane for efficient separation of gas mixtures, comprising the following steps: (1) dissolving an initial PDMS, a cross-linking agent and a catalyst in a first solvent, mixing and stirring to cause a prepolymerization reaction of the initial PDMS to obtain a PDMS casting solution; (2) using the supporting layer ultrafiltration membrane as a suction filtration membrane of a dead-end filtration system, and testing the retention rate of the supporting layer ultrafiltration membrane for the PDMS casting solution of step (1); (3) If the retention rate measured in step (2) is greater than or equal to 90%, proceed to step (4); otherwise, it is necessary to increase the degree of prepolymerization of the PDMS casting solution in step (1) or increase the molecular weight of the initial hydroxyl-terminated polydimethylsiloxane until the retention rate of the casting solution obtained after the prepolymerization reaction measured in step (2) is greater than or equal to 90%; (4) transferring the PDMS casting solution corresponding to the measured retention rate greater than or equal to 90% to the surface of the support layer ultrafiltration membrane of step (2), scraping and drying to remove excess first solvent, thereby obtaining a PDMS membrane; the support layer ultrafiltration membrane and the porous ultrafiltration membrane of step (2) are ultrafiltration membranes of the same model; (5) dissolving the polyether block polyamide in a second solvent to obtain a Pebax casting solution; transferring the Pebax casting solution to the surface of the PDMS membrane, scraping and drying to remove excess solvent, and preparing a Pebax selection layer on the surface of the PDMS membrane, thereby obtaining the high-throughput composite membrane.
[0033] The high-flux middle layer is the basis of the high-flux composite membrane. However, during the preparation of the middle layer, the low-concentration casting solution will inevitably penetrate into the pores of the porous support layer. The pore permeation phenomenon will increase the actual thickness of the middle layer and reduce the flux. Increasing the concentration of the casting solution will increase the thickness of the middle layer and reduce the flux of the composite membrane (usually the thinner the middle layer, the higher the flux). The existing technology modifies the end groups of PDMS to achieve rapid cross-linking of PDMS, and uses the end-group-modified PDMS to form a network structure to prevent pore permeation. However, this method will increase material costs and complicate the preparation process. During the experiment of the present invention, an attempt was made to investigate the relationship between the degree of PDMS prepolymerization in the PDMS casting solution and the PDMS porosity, a test model for the interception rate of the PDMS casting solution on the surface of the supporting layer ultrafiltration membrane was established, and a new idea for preparing a high-flux composite membrane was proposed. The interception rate threshold with both composite membrane flux and selectivity was found through experiments, and the interception rate of the PDMS casting solution on the surface of the supporting layer ultrafiltration membrane was greater than or equal to the threshold by regulating the degree of PDMS prepolymerization in the PDMS casting solution or increasing the molecular weight of the initial hydroxyl-terminated polydimethylsiloxane. In this way, the interception rate of the PDMS casting solution on the surface of the supporting layer ultrafiltration membrane was cleverly used to reflect the porosity, solving the porosity problem of PDMS in the supporting layer, and preparing a composite membrane with excellent flux and selectivity. The preparation method of the composite membrane of the present invention can be applied to PDMS with any initial molecular weight, and there is no absolute restriction and requirement on the pore size of the supporting layer ultrafiltration membrane. According to the preparation method of the present invention, only the PDMS casting solution and the supporting layer ultrafiltration membrane need to be relatively matched.
[0034] Dead-end filtration systems are usually used to intercept substances in liquid systems using filter media (such as ultrafiltration membranes, etc.). This application is based on the inventive idea of intercepting PDMS prepolymer liquid by the support layer ultrafiltration membrane to prevent its pore permeability from affecting the performance of the composite membrane. The dead-end filtration system is used to first test the interception rate of the selected support layer ultrafiltration membrane for PDMS casting liquid, set the interception rate threshold, and select PDMS prepolymer liquid greater than or equal to the interception rate threshold for subsequent composite membrane preparation. Experiments show that this inventive idea can indeed prepare defect-free, high-throughput and high-selectivity composite membranes.
[0035] In step (2), the retention rate is calculated by analyzing the PDMS concentration in the initial PDMS casting solution and the PDMS casting solution on the permeate side using hydrogen nuclear magnetic resonance spectroscopy.
[0036] Specifically, the rejection rate = (the concentration of PDMS in the initial PDMS solution - the concentration of PDMS in the PDMS solution on the permeate side) / the concentration of PDMS in the initial PDMS solution × 100%.
[0037] In some embodiments, the concentration of PDMS is calculated by using the area normalization method based on the peak areas of characteristic hydrogen atoms in the PDMS in the solution and in the first solvent. The calculation formula is shown in formula (1):
[0038] Where: c i is the concentration of PDMS in the test solution, wt%; A i and A k Respectively represent the characteristic hydrogen atom peak areas of PDMS and the first solvent in the test solution; n i and n k Respectively represent the characteristic hydrogen atoms of PDMS and the first solvent in the test solution; m i and m k Respectively represent the relative molecular weights of PDMS and the first solvent in the test solution.
[0039] In some embodiments, during the calculation process, assumptions are made about the number of –Si(CH3)2O– unit repetitions and the number of PDMS segments of all PDMS molecules, which are set as x and y, respectively. Therefore, the relative molecular weight of the PDMS prepolymer in the solution can be expressed as 74x+18y, the relative molecular weight of –Si(CH3)2O– is 74, and the sum of the relative molecular weights of the hydroxyl groups and hydrogen atoms at both ends of the PDMS segment is 18.
[0040] Taking n-heptane as the first solvent, the hydrogen atoms on the methyl groups at both ends of the n-heptane molecule and the hydrogen atoms on the methyl groups connected to the silicon atom of PDMS are respectively used as characteristic hydrogen atoms. Since the hydrogen atoms on the methyl groups at both ends of the n-heptane molecule and the hydrogen atoms on the methyl groups connected to the silicon atom of PDMS are both symmetrical structures, each hydrogen atom is 1 The chemical shifts in the H NMR test are the same. The n-heptane molecule has 6 characteristic hydrogen atoms, while each silicon atom of PDMS has 6 characteristic hydrogen atoms, a total of 6x. 1 The H NMR results were analyzed, and the characteristic peak area of hydrogen atoms corresponding to n-heptane of the first solvent was defined as 6, and the peak area of hydrogen atoms corresponding to PDMS was obtained; Based on the above assumptions, the concentration of PDMS in the test solution is calculated as follows:
[0041] In formula (2), the molecular weight 18y of the hydroxyl groups at both ends of PDMS is much smaller than the molecular weight 74x of the repeating unit –Si(CH3)2O–, so 18y is ignored to simplify the calculation; 1 The concentration of PDMS was determined from the peak intensity of H NMR.
[0042] In some embodiments, the first solvent is n-heptane and / or n-hexane, and the concentration of PDMS in the PDMS casting solution is 0.2 wt%-3wt%, and more preferably 0.2 wt%-1.5wt%.
[0043] In some embodiments, the mass ratio of the polydimethylsiloxane (PDMS), the cross-linking agent and the catalyst in step (1) is 100: (10-50): (1-50).
[0044] In some embodiments, the mixing and stirring in step (1) is carried out at room temperature (20-30° C.) for 20 min-240 min, preferably 30 min-60 min. In some embodiments, the crosslinking agent is tetraethyl orthosilicate, TEOS; and the catalyst is dibutyltin dilaurate, DBTDL.
[0045] The supporting layer ultrafiltration membrane in step (4) is the same type of ultrafiltration membrane as the porous ultrafiltration membrane in step (2); it can adopt the porous ultrafiltration membrane material commonly used in the prior art. In some embodiments, the ultrafiltration membrane is PSF, PAN or PVDF, etc.
[0046] In some embodiments, the step (4) of transferring the PDMS casting solution to the surface of the supporting layer ultrafiltration membrane can be transferred to the surface of the supporting layer ultrafiltration membrane by dripping, etc. Similarly, the step (5) of transferring the Pebax casting solution to the surface of the PDMS membrane by dripping can also be performed.
[0047] In some embodiments, the drying in step (4) is performed by heating at 60-80° C. for 0.5-4 h; and / or the thickness of the PDMS film is about 200-400 nm.
[0048] In some embodiments, the second solvent in step (5) is a mixed solvent of ethanol and water or n-butanol; the concentration of Pebax in the Pebax casting solution in step (5) is 1 mg / mL-20 mg / mL; the drying in step (5) is heating at 60-80°C for 4-12 h; the thickness of the Pebax selection layer in step (5) is 131 nm-1.38 μm.
[0049] In some embodiments, the Pebax brand is Pebax ® 1657、Pebax ® 2533、Pebax ® 3533、Pebax ® 4033、Pebax ® 6333 or any combination thereof.
[0050] In some embodiments, after obtaining the PDMS membrane in step (4), the method further comprises the step of: using an atmospheric plasma cleaning machine to hydrophilically modify the surface of the PDMS membrane to obtain a hydrophilically modified PDMS membrane. In a preferred embodiment, the atmospheric plasma treatment conditions are a treatment speed of 25-40 mm / s, a power of 800-1000 W, and a working distance of 1-3 cm.
[0051] The process parameters without specific conditions in the following examples are usually based on conventional conditions.
[0052] The embodiments of the present application are described below in conjunction with the drawings of the embodiments of the present application.
[0053] Firstly, a dead-end filtration system was used to test the retention rate of the porous support layer for PDMS with different molecular weights. A total of five PDMS with molecular weights of 15 kDa, 58 kDa, 90 kDa, 167 kDa and 347 kDa were selected. The porous support layer used was PSF, and its retention molecular weight was 63 kDa (data provided by the merchant, test results using polyethylene glycol as the standard substance).
[0054] The retention rate is calculated by using nuclear magnetic resonance hydrogen spectrum to analyze the PDMS concentration in the initial solution and the permeate side solution. The specific analysis method is: The concentration of PDMS can be calculated by the area normalization method based on the characteristic hydrogen atom peak areas of PDMS in the solution and the first solvent n-heptane, as shown in formula (1).
[0055]
[0056] Where: c i is the concentration of PDMS in the test solution, wt%; A i and A k Respectively represent the characteristic peak areas of PDMS and n-heptane in the test solution; n i and n k Respectively represent the number of hydrogen atoms of PDMS and the first solvent in the test solution; m i and m k represent the relative molecular weights of PDMS and the first solvent in the test solution respectively; in the calculation process, assumptions are made on the number of –Si(CH3)2O– unit repetitions and the number of PDMS segments of all PDMS molecules, which are set as x and y respectively. Therefore, the relative molecular weight of the PDMS prepolymer in the solution can be expressed as 74x+18y, the relative molecular weight of –Si(CH3)2O– is 74, and the sum of the relative molecular weights of the hydroxyl groups and hydrogen atoms at both ends of the PDMS segment is 18.
[0057] Based on the above assumptions, the concentration of PDMS in the solution is calculated as:
[0058] The molecular weight of the hydroxyl groups at both ends of PDMS in formula (2) (18y) is much smaller than the molecular weight of the repeating unit –Si(CH3)2O– (74x), so 18y can be ignored to simplify the calculation. The characteristic peak area A of n-heptane k Assume it is 6. Number of hydrogen atoms n k is 6, and the molecular weight is 100. 1 The concentration of PDMS was determined from the peak intensity of H NMR.
[0059] Taking the PSF ultrafiltration membrane with a molecular weight cutoff of 63 kDa as an example, the test results of the nuclear magnetic resonance hydrogen spectrum are as follows: Figure 1 The detailed calculation results of the interception rate are shown in Table 1 below.
[0060] Table 1
[0061] Note: The first row corresponding to each molecular weight PDMS is the initial PDMS concentration before filtration, and the second row is the PDMS concentration on the permeate side after filtration.
[0062] a) Number of repeating units of –Si(CH3)2O– in PDMS b) Number of PDMS segments The test results of the interception rate are as follows: Figure 2 As shown. For the PSF ultrafiltration membrane with a molecular weight cutoff of 63 kDa, when the mass fraction of PDMS is 0.1 wt% (n-heptane is the solvent), the retention rate of the support layer for PDMS molecules with molecular weights of 15 kDa and 53 kDa is only 5.5% and 11.4%, indicating that low molecular weight PDMS can easily penetrate (pass through) the pores of the support layer. When the molecular weight is increased above 63 kDa, the retention rate is significantly improved. The retention rates of the support layer for PDMS molecules of 90 kDa, 167 kDa and 347 kDa are 49.9%, 50.6% and 65.6%, respectively. For the PSF support layer ultrafiltration membrane with a molecular weight cutoff of 20 kDa, the retention rates of the support layer for PDMS molecules of 53 kDa, 90 kDa, 167 kDa and 347 kDa are 57.2%, 65.9%, 76.6% and 86.3%, respectively. It can be seen that for any type of supporting layer ultrafiltration membrane, the retention rate of the supporting layer for PDMS with different molecular weights can be obtained by adjusting the initial PDMS molecular weight.
[0063] In this example, vacuum filtration was also used to directly filter and form a membrane on the surface of a porous support layer (MWCO: PSF of 63 kDa), and scanning electron microscopy and gas flux testing were used to verify the matching relationship between the PDMS molecular weight and the pore size of the support layer: the vacuum filtration method was used because the concentration of the casting solution used in vacuum filtration is relatively low, which can eliminate as much as possible the influence of the concentration-induced clustering between polymers on the experimental results.
[0064] The experimental steps of vacuum filtration are: (1) Fix the PSF ultrafiltration membrane in a filtration bottle as a filtration membrane, and use water-ethanol-water-ethanol to repeatedly vacuum filter to remove the pore-filling agent in the ultrafiltration membrane. (2) Take 10 mL of n-heptane solution of PDMS with different molecular weights (PDMS mass fraction is 0.1 wt%) and add it to the filtration bottle. The solution passes through the ultrafiltration membrane under the action of vacuum filtration.
[0065] (3) After the solution in step (2) is completely drained, the membrane is transferred to a 60° C. oven for drying to remove excess solvent, thereby obtaining the separation membrane.
[0066] Figure 3 The surface and cross-sectional SEM of the PDMS intermediate layer obtained by vacuum filtration. With the SEM image, it can be observed that as the molecular weight of PDMS increases, the membrane surface gradually changes from rough to smooth. At the same time, when the PDMS molecular weight is higher than the molecular weight cutoff of the support layer, the cross-sectional SEM image shows that a polymer layer appears on the surface of the PSF, and the thickness increases from 683 nanometers to 2.07 microns, indicating that the high molecular weight PDMS is indeed more retained on the surface of the support layer, rather than infiltrating (passing through) the pores of the support layer, which is consistent with the test results of the interception rate.
[0067] Example 1 Preparation of high-throughput PDMS intermediate layer: 1. Weigh 0.05 g of PDMS (molecular weight 90 kDa), add it to 8.95 g of n-heptane, fully dissolve and stir to obtain solution A. Prepare four groups of solution A.
[0068] 2. Add 0.025 g of TEOS and 0.025 g of DBTDL to each of the four solutions A to obtain solution B, and stir at a constant temperature of 25°C.
[0069] 3. The four groups of solutions were prepolymerized for 5, 10, 20, and 30 min, respectively. After the prepolymerization time was reached, 2.5 mL of solution B prepared in step 2 above (wherein the mass fraction of PDMS was 0.5 wt%) was taken and dropped onto the surface of four commercial PSF ultrafiltration membranes (molecular weight cutoff: 63 kDa), and the PDMS composite membranes obtained by rapid scraping with a 100 μm thick scraper were transferred to an 80 ℃ oven and heated for 2 h for use.
[0070] 4. The remaining solution was dead-end filtered to test the retention rate of PSF ultrafiltration membrane for PDMS casting solution with different prepolymerization times.
[0071] Figure 4 and Figure 5 This is the carbon dioxide / nitrogen pure gas separation performance of the PDMS composite membrane with different prepolymerization times prepared in this example. Figure 5 In the bar graph, the red filled area represents the retention rate, the green filled area represents the carbon dioxide gas flux, and the purple filled area represents the carbon dioxide / nitrogen selectivity. For PDMS with a molecular weight of 90 kDa, as the prepolymerization time increases from 10 minutes to 20 minutes, the carbon dioxide / nitrogen selectivity increases significantly from 1.4 to 10.6. When the prepolymerization time is 30 minutes, the separation performance reaches the best, with a carbon dioxide flux of 9471 GPU and a carbon dioxide / nitrogen selectivity of 10.6. For comparison, the figure also shows the carbon dioxide / nitrogen pure gas separation performance of PDMS with an initial molecular weight of 15 kDa under the same prepolymerization conditions. It can be seen that within the 30-minute prepolymerization time, the flux and selectivity do not change significantly, which is close to the porous support layer. This may be due to the fact that the retention rate of PDMS for PSF with a molecular weight cutoff of 15kDa within the 30-minute prepolymerization time is less than 90%.
[0072] Figure 6 Content (a) and content (b) are scanning electron micrographs of the surface and cross section of the PDMS composite membrane with a prepolymerization time of 30 min, respectively. Figure 1 It can be seen from content (b) that the thickness of the PDMS intermediate layer is about 300 nm.
[0073] Figure 7 The retention rate of PDMS by PSF was tested according to the above method when 0.5 wt% PDMS was prepolymerized for 0min and 30min. The retention rate increased from 52.7% before prepolymerization to 93.2%. (Although the prepolymer solution contains crosslinking agent and catalyst in addition to PDMS and n-heptane, when the retention rate is calculated based on the characteristic hydrogen atom peak area using the area normalization method, PDMS and n-heptane are still taken as a whole 1, and the parameters of the two are taken to calculate according to formulas (1) and (2) because the positions of the characteristic hydrogen atom peaks of different substances are different).
[0074] Table 2 shows the flux and selectivity test results of the PDMS composite membrane prepared under different conditions in Example 1 for a carbon dioxide / nitrogen mixed gas.
[0075] Table 2
[0076] It can be seen from Table 2 that for PDMS with an initial concentration of 0.5%, as the prepolymerization time increases, the retention rate of PDMS on the support layer ultrafiltration membrane increases and the flux of the mixed gas decreases, but unexpectedly, the selectivity of CO2 / N2 increases from 0.9 corresponding to 5 minutes of prepolymerization to 10.9 corresponding to 30 minutes of prepolymerization (corresponding to a retention rate of 93.2%), while the flux of CO2 can still be maintained at 9471GPU.
[0077] The separation performance of carbon dioxide and pure nitrogen was compared between the PDMS intermediate layer material prepared in Example 1 (molecular weight 90 kDa, 0.5 wt% PDMS prepolymerized for 30 minutes) and the composite membrane intermediate layer material prepared by the prior art, as shown in Table 3.
[0078] Table 3
[0079] Compared with the composite membranes of the prior art, the intermediate layer material of the composite membrane prepared in the embodiment of the present invention has a selectivity of more than 10 and a carbon dioxide flux of up to 9471 GPU, which is much higher than the composite membranes No. 1 to 5 which are also OH-PDMS. Although the intermediate layer material AC-PDMS prepared in reference [9] also has high carbon dioxide selectivity and flux, its terminal group is acryloyloxy, which requires free radical polymerization under anaerobic conditions, which greatly limits its practical application.
[0080] References: [1] X. Xu, J. Dong, X. Xiao, X. Zhao, Q. Zhang. Constructing thin and cross-linked polyimide membranes by interfacial reaction for efficientCO2separation. ACS Sustainable Chemistry&Engineering. 2021, 9(16): 5546-5556. [2] X. Jiang, K. Goh, R. Wang. Air plasma assisted spray coating ofPebax-1657 thin-film composite membranes for post-combustion CO2capture.Journal of Membrane Science. 2022, 658: 120741. [3] P. Li, Z. Wang, W. Li, Y. Liu, J. Wang, S. Wang. High-performancemultilayer composite membranes with mussel-inspired polydopamine as aversatile molecular bridge for CO2separation. ACS Applied Materials&Interfaces. 2015, 7(28): 15481- 15493. [4] C. Z. Liang, T. S. Chung. Ultrahigh flux composite hollow fibermembrane via highly crosslinked PDMS for recovery of hydrocarbons: propaneand propene. Macromolecular Rapid Communications. 2018, 39(5): 1700535. [5] P. Li, H. Z. Chen, T. Chung. The effects of substratecharacteristics and pre-wetting agents on PAN–PDMS composite hollow fibermembranes for CO2 / N2and O2 / N2separation. Journal of Membrane Science. 2013,434: 18-25. [6] Q. Fu, A. Halim, J. Kim, JMP Scofield, PA Gurr, SEKentish, et al. Highly permeable membrane materials for CO2capture. Journal of Materials Chemistry A. 2013, 1(44): 13769. [7] A. Halim, Q. Fu, Q. Yong, PA Gurr, SE Kentish, GG Qiao.Soft polymeric nanoparticle additives for next generation gas separation membranes. Journal of Materials Chemistry A. 2014, 2(14): 4999-5009. [8] JMP Scofield, PA Gurr, J. Kim, Q. Fu, SE Kentish, GG Qiao. Development of novel fluorinated additives for high performanceCO2separation thin-film composite membranes. Journal of Membrane Science.2016, 499: 191-200. [9] Y. Pan, G. Chen, J. Liu, J. Li, X. Chen, H. Zhu, et al. PDMSthin-film composite membrane fabricated by ultraviolet crosslinkingacryloyloxy-terminated monomers. Journal of Membrane Science. 2022, 658:120763. Preparation of mPDMS by atmospheric plasma surface hydrophilic modification: The principle of atmospheric plasma treatment is to break the Si-C bond on the PDMS surface and introduce hydroxyl groups on the silicon atoms to form a silicon dioxide-like structure SiO x .SiO xAlthough the structure improves the hydrophilicity of the PDMS surface, it also hinders the transmission of gas, resulting in a decrease in gas flux. Figure 8 The trend of the change of carbon dioxide and surface water contact angle at different atmospheric plasma treatment times. Extending the treatment time from 0 seconds to 2.8 seconds can reduce the carbon dioxide flux from 9471 GPU to 3941 GPU, and the water contact angle from 107° to 56°. Taking all factors into consideration, 2.0 seconds of atmospheric plasma treatment was selected as the condition for preparing the hydrophilic modified PDMS interlayer, with a carbon dioxide permeability of 4976 GPU and a water contact angle of 72.1°.
[0081] Preparation and separation performance of Pebax / PDMS / PSF composite membrane Preparation of Pebax / PDMS / PSF composite membrane: 1. Preparation of PDMS composite membrane: 1.1 Weigh 0.05 g of PDMS, add it to 8.95 g of n-heptane, and dissolve it thoroughly with stirring to obtain solution A.
[0082] 1.2 Add 0.025 g of TEOS and 0.025 g of DBTDL to solution A and stir at 25 °C for 30 min to obtain solution B.
[0083] 1.3 Take 2.5 mL of solution B (PDMS mass fraction is 0.5 wt%) prepared in step 1.2 above, drop it on the surface of the commercial ultrafiltration membrane, and quickly scrape it with a scraper with a thickness of 100 μm.
[0084] 1.4 Transfer the PDMS composite membrane obtained in step 1.3 to an 80 °C oven and heat for 2 h for later use.
[0085] 2. Preparation of hydrophilic modified mPDMS composite membrane 2.1 Place the PDMS membrane obtained in step 1 into an atmospheric plasma cleaning machine and set the parameters to process power 800 W, process height 1.2 cm, and nozzle moving speed 35 mm / s.
[0086] 2.2 Set the nozzle moving path and treat the PDMS membrane surface along the Z-shape to obtain the mPDMS membrane.
[0087] 3. Preparation of Pebax composite film 3.1 Dissolve 0.5 g Pebax ® The 1657 particles were dissolved in a mixed solution of 30 mL of deionized water and 70 mL of ethanol and stirred at 70 °C for 5 h to obtain a uniform solution C (the mass-volume concentration of Pebax was 5 mg / mL).
[0088] 3.2 Solution C was diluted with a mixed solution of ethanol / water (v / v=7 / 3) to a Pebax mass-volume concentration of 3 mg / mL. 2.5 mL of the casting solution was added dropwise onto the surface of the mPDMS membrane and quickly scraped with a scraper with a thickness of 100 μm.
[0089] 3.3 The Pebax membrane obtained in step 3.2 was transferred to an oven at 80 °C and heated for 4 h to evaporate the excess solvent, and then a Pebax selective layer was prepared on the surface of the mPDMS membrane to prepare a composite membrane.
[0090] Scanning electron microscope photos of the PSF ultrafiltration membrane surface Fig. 9 As shown in content (a), the surface scanning electron microscope photo of Pebax composite film is as follows Fig. 9 Content (b) shows that the cross-sectional scanning electron microscope Fig. 9 As shown in content (c), it can be seen from the figure that Pebax is uniformly loaded on the membrane surface, and the total thickness of the Pebax layer and the PDMS layer is 554 nm.
[0091] Fig.10 The pure gas flux of the Pebax composite membrane prepared in this example is 432 GPU for carbon dioxide, 273 GPU for propylene, 24 GPU for methane, and 9 GPU for nitrogen. The selectivity of propylene / nitrogen is 30, the selectivity of carbon dioxide / methane is 18, and the selectivity of carbon dioxide / nitrogen is 48.
[0092] Fig.11 The Pebax composite membrane prepared in this example was tested for 80 hours in a mixed gas mixture, and its gas flux and propylene / nitrogen selectivity changed. As can be seen from the figure, by changing the test pressure and feed gas composition, the propylene flux of the composite membrane is 200 GPU, and the propylene / nitrogen selectivity remains above 20.
[0093] Fig.12 The carbon dioxide / methane mixed gas separation performance of the Pebax composite membrane prepared in this example is shown in Figure 2. The carbon dioxide flux is 366 GPU, the methane flux is 30 GPU, and the carbon dioxide / methane selectivity is 12 (the test conditions are a carbon dioxide to methane volume ratio of 50:50, a test temperature of 25 °C, and a test pressure of 2 bar).
[0094] Table 4
[0095] The preparation conditions were the same as those of the Pebax / PDMS / PSF composite membrane in Example 1. Different types of mixed gases were tested at different Pebax mass-volume concentrations. The flux and selectivity test results of the mixed gases are shown in Table 4.
[0096] It can be seen from Table 4 that the composite membrane prepared according to the preparation method of this embodiment is suitable for a variety of mixed gas systems. For the CO2 / CH4 mixed gas system, when the concentration of Pebax is 3 mg / mL, the CO2 / CH4 selectivity can reach more than 11, and the CO2 flux is 365.8 GPU. For the C3H6 / N2 mixed gas system, when the concentration of Pebax is 3 mg / mL, the C3H6 / N2 selectivity can reach more than 21, and the C3H6 flux is 209.9 GPU.
[0097] Example 2 Preparation of Pebax composite membrane 1. Preparation of PDMS intermediate layer 1.1 Weigh 0.05 g of PDMS, add it to 8.95 g of n-heptane, and dissolve it thoroughly with stirring to obtain solution A.
[0098] 1.2 Add 0.025 g of TEOS and 0.025 g of DBTDL to solution A and stir at 25 °C for 30 min to obtain solution B.
[0099] 1.3 Take 2.5 mL of solution B (PDMS mass fraction is 0.5 wt%) prepared in step 1.2 above, drop it on the surface of the commercial ultrafiltration membrane, and quickly scrape it with a scraper with a thickness of 100 μm.
[0100] 1.4 Transfer the PDMS composite membrane obtained in step 1.3 to an 80 °C oven and heat for 2 h for later use.
[0101] 2. Preparation of Pebax composite film 2.1 Dissolve 1.5 g of Pebax 1657 particles in 100 mL of n-butanol solution and stir at 125 °C for 5 h to obtain a uniform solution C (the mass-volume concentration of Pebax is 15 mg / mL).
[0102] 2.2 Take 2.5 mL of solution C and drop it on the surface of the mPDMS membrane. Use a scraper with a thickness of 100 μm to quickly scrape it.
[0103] 2.3 The Pebax film obtained in step 3.2 was transferred to an oven at 80°C and heated for 4 h to evaporate the excess solvent, thereby obtaining the Pebax composite film of the present invention.
[0104] In this example, since n-butanol has good affinity with PDMS, the atmospheric plasma hydrophilic modification step can be omitted.
[0105] The Pebax composite membrane prepared in this example has a carbon dioxide flux of 142 GPU, a nitrogen flux of 2.7 GPU, and a carbon dioxide / nitrogen selectivity of 52.6 (the test conditions are pure gas, the test temperature is 25 °C, and the test pressure is 2 bar).
[0106] Example 3 Preparation of Pebax composite membrane 1. Preparation of PDMS intermediate layer 1.1 Weigh 0.05 g of PDMS (molecular weight 90 KDa), add it to 8.95 g of n-heptane, and dissolve and stir thoroughly to obtain solution A.
[0107] 1.21 Add 0.025 g of TEOS and 0.025 g of DBTDL to solution A and stir at 25 °C for 10 min to obtain solution B1.
[0108] 1.22 The retention rate of the prepolymer solution B1 on the PSF ultrafiltration membrane (molecular weight cutoff: 63 kDa) was tested by the above retention rate test method, and the retention rate was measured to be less than 90%. Therefore, the prepolymer solution was continued to be stirred at a constant temperature of 25°C for 20 min to obtain solution B2; the retention rate of the prepolymer solution B2 was measured again to be 93.8%, which is greater than 90%.
[0109] 1.3 Take 2.5 mL of solution B2 (PDMS mass fraction is 0.5 wt%) prepared in step 1.22 above, drop it on the surface of PSF ultrafiltration membrane, and quickly scrape it with a scraper with a thickness of 100 μm.
[0110] 1.4 Transfer the PDMS membrane obtained in step 1.3 to an 80 °C oven and heat for 2 h for later use.
[0111] 2. Preparation of Pebax composite film 2.1 Dissolve 1.5 g of Pebax 1657 particles in 100 mL of n-butanol solution and stir at 125 °C for 5 h to obtain a uniform solution C (the mass-volume concentration of Pebax is 15 mg / mL).
[0112] 2.2 Take 2.5 mL of solution C and drop it on the surface of the mPDMS membrane. Use a scraper with a thickness of 100 μm to quickly scrape it.
[0113] 2.3 The Pebax film obtained in step 3.2 was transferred to an oven at 80°C and heated for 4 h to evaporate the excess solvent, thereby obtaining the Pebax composite film of the present invention.
[0114] The present invention adopts a bottom-up layer-by-layer optimization scheme to improve the flux of the composite membrane, and prepares a high-flux intermediate layer by avoiding the pore permeation of the PDMS casting liquid, mainly solving the problem of low gas processing flux in the current composite membrane used for gas mixture separation. First, a high-flux commercial ultrafiltration membrane is selected as a porous support layer to provide mechanical strength for the composite membrane. By directly testing the retention rate of the support layer for the PDMS casting liquid, the subsequent support layer scraping and selective layer preparation are carried out only when the retention rate is greater than 90%, otherwise the PDMS is continued to be prepolymerized, so as to ensure that the PDMS can be retained by the substrate on the surface of the support layer, avoiding the pore permeation phenomenon, thereby facilitating the improvement of the flux of the final composite membrane when separating mixed gases; different support layers and different initial PDMS molecular weights can be applied according to the method of the present invention, and the retention rate is controlled by controlling the degree of prepolymerization, so as to achieve high-flux and high-selectivity separation of gases.
[0115] The present invention realizes the successful preparation of an ultra-thin, high-throughput PDMS middle layer. Experiments show that by controlling the interception rate of the prepolymer liquid on the surface of the support layer, it is ensured that the PDMS can be effectively intercepted by the support layer to the surface, avoiding the phenomenon of pore permeation. In a preferred embodiment, the thickness of the obtained PDMS middle layer is about 300 nanometers, and its carbon dioxide and propylene pure gas fluxes are 9471 GPU and 20785 GPU, respectively. After obtaining a high-throughput PDMS middle layer, in order to improve the affinity between the middle layer and the selection layer, atmospheric plasma treatment that can be treated over a large area is used to hydrophilically modify the PDMS, providing feasibility for industrial large-scale production. Subsequently, by optimizing the solvent, concentration and other parameters of the Pebax casting solution, a high-throughput Pebax composite membrane was successfully prepared in combination with a scraping method.
[0116] The above is only a specific implementation of the present application, but the protection scope of the present application is not limited thereto. Any person skilled in the art who is familiar with the present technical field can easily think of changes or substitutions within the technical scope disclosed in the present application, which should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.
Claims
1. A method for preparing a high-throughput composite membrane for efficient separation of gas mixtures, characterized in that: The steps include: (1) dissolving an initial hydroxyl-terminated polydimethylsiloxane, a crosslinking agent, and a catalyst in a first solvent, mixing and stirring to cause a prepolymerization reaction of the initial hydroxyl-terminated polydimethylsiloxane to obtain a PDMS casting solution; (2) using the porous ultrafiltration membrane as a suction filtration membrane of a dead-end filtration system, and testing the retention rate of the porous ultrafiltration membrane for the PDMS casting solution of step (1); (3) If the retention rate measured in step (2) is greater than or equal to 90%, proceed to step (4); otherwise, increase the degree of prepolymerization of the PDMS casting solution in step (1) or increase the molecular weight of the initial hydroxyl-terminated polydimethylsiloxane so that the retention rate of the casting solution measured in step (2) is greater than or equal to 90%; (4) transferring the PDMS casting solution corresponding to the measured retention rate greater than or equal to 90% to the surface of the supporting layer ultrafiltration membrane, scraping and drying to remove excess first solvent, thereby obtaining a PDMS membrane; the supporting layer ultrafiltration membrane and the porous ultrafiltration membrane of step (2) are ultrafiltration membranes of the same model; (5) dissolving the polyether block polyamide in a second solvent to obtain a Pebax casting solution; transferring the Pebax casting solution to the surface of the PDMS membrane, scraping and drying to remove excess second solvent, and preparing a Pebax selection layer on the surface of the PDMS membrane, thereby obtaining the high-flux composite membrane.
2. The preparation method according to claim 1, characterized in that In step (2), the porous ultrafiltration membrane is used as a suction filtration membrane of the dead-end filtration system, and the retention rate is calculated by analyzing the PDMS concentration in the initial PDMS casting solution and the PDMS casting solution on the permeate side before and after filtration of the dead-end filtration system using nuclear magnetic resonance hydrogen spectrum.
3. The preparation method according to claim 2, characterized in that: The concentration of PDMS in the test solution is calculated by using the area normalization method according to the characteristic hydrogen atom peak areas of PDMS in the test solution and the first solvent, wherein the test solution includes the initial PDMS casting solution and the PDMS casting solution on the osmotic side. The calculation formula for the concentration of PDMS in the test solution is shown in formula (1): Where: c i is the concentration of PDMS in the test solution, wt%; A i and A k Respectively represent the characteristic hydrogen atom peak areas of PDMS and the first solvent in the test solution; n i and n k Respectively represent the characteristic hydrogen atoms of PDMS and the first solvent in the test solution; m i and m k Respectively represent the relative molecular weights of PDMS and the first solvent in the test solution.
4. The preparation method according to claim 1, characterized in that: The first solvent is n-heptane and / or n-hexane, and the concentration of PDMS in the PDMS casting solution is 0.2 wt%-3 wt%; and / or, The mixing and stirring in step (1) is carried out at 25-35° C. for 20 min-240 min.
5. The preparation method according to claim 1, characterized in that: Step (3) improving the prepolymerization degree of the PDMS casting solution in step (1) so that the retention rate of the casting solution obtained after the prepolymerization reaction measured in step (2) is greater than or equal to 90%, specifically: increasing the prepolymerization degree by extending the time of the prepolymerization reaction in step (1) so that the retention rate of the casting solution is greater than or equal to 90%.
6. The preparation method according to claim 1, characterized in that: The crosslinking agent is tetraethyl orthosilicate; the catalyst is dibutyltin dilaurate; and / or, The porous ultrafiltration membrane in step (2) and the supporting layer ultrafiltration membrane in step (4) are PSF, PAN or PVDF.
7. The preparation method according to claim 1, characterized in that: The drying in step (4) is performed by heating at 60-80°C for 0.5-4 h; and / or, In step (5), the second solvent is a mixed solvent of ethanol and water or n-butanol; and / or, The concentration of Pebax in the Pebax casting solution in step (5) is 1 mg / mL-20 mg / mL; and / or, The drying in step (5) is performed by heating at 60-80°C for 4-12 hours.
8. The preparation method according to claim 1, characterized in that: After the PDMS membrane is obtained in step (4), the method further comprises the step of: using an atmospheric plasma cleaning machine to perform hydrophilic modification on the surface of the PDMS membrane to obtain a hydrophilically modified PDMS membrane.
9. The high-flux composite membrane prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the high-flux composite membrane according to claim 9 in separation of gas mixtures.
Citation Information
Patent Citations
Polyether block polyamide / polydimethylsiloxane composite gas separation membrane, preparation method and application
CN115608177A
PDMS (polydimethylsiloxane) gas separation composite membrane with controllable pore permeability depth and preparation method of PDMS gas separation composite membrane
CN117339405A
Acryloyloxy-terminated polydimethylsiloxane (ac-PDMS)-based thin-film composite (TFC) membrane, and preparation method and use thereof
US20230398504A1